Rectus Sheath Hematoma Causing Bladder Outlet Obstruction - Gupta, Anupam K (Cureus, 2020)
A 93-year-old woman on Coumadin with history of atrial fibrillation and chronic obstructive pulmonary disease (COPD) presented with urinary retention for one day. Computed tomography (CT) of abdomen and pelvis demonstrated grade 3 rectus sheath hematoma (RSH), with the hematoma dissecting between the transversalis fascia and muscle into the prevesical space. The large-sized hematoma caused compression at the bladder outflow tract causing urinary retention. In view of age and the patient being a poor surgical candidate, the patient was managed by percutaneous drain of the hematoma to reduce size to relieve urinary symptoms. The hematoma shrunk in size over the period of next few weeks and thereby avoided surgical intervention.